Phytochemical Screening and in vitro Antimicrobial Activity of Extracts from Tubers of Wild Dioscorea species - Salunke, Chetana Anand; Satpute, Rajendra A (JOURNAL OF ROOT CROPS, 2018)
Genus Dioscorea of the family Dioscoreaceae, is a herbaceous annual vine plant. Some Dioscorea species are important food crops producing tubers and bulbils rich in medicinal value. Phytochemical screening was carried out and the in vitro antimicrobial activities of tuber extracts of D. bulbifera L., D. alata L., D. esculenta (Lour.) Burkill. and D. pentaphylla L. were assessed using standard techniques. Qualitative analysis for phytochemicals present in tuber extracts confirmed the presence of alkaloids, saponins, flavonoids, phenols, carbohydrates, proteins, glycosides and steroids. Tuber extracts of all the Dioscorea species exhibited inhibitory activity against all bacterial and fungal pathogens tested. The study demonstrated that tested Dioscorea species contains phytochemicals with antimicrobial properties and hence are potential medicinal dietary plant.